Palaeomagnetic Results from the Arrochar and Garabal Hill-Glen Fyne Igneous Complexes, Scotland - Briden, J. C. (Geophysical Journal International, 1970)
From the Arrochar intrusive complex and its contact aureole 47 cores from N = 6 sites (mean co-ordinates 56° 14′ N, 4° 48′ W) yield a stable NRM direction after magnetic cleaning D = 213.3°, I = +36.6° (κ = 166.7). Calculated mean K-Ar age is 418 My. From a total collection of 37 cores from 11 sites in the Garabal Hill-Glen Fyne complex, a mean stable NRM direction after magnetic cleaning D = 32.2°, I = ™42.5° (κ = 11.1) was determined from N = 5 sites (mean coordinates 56° 18′ N, 4° 47′ W) with supporting evidence from a further two sites. Best estimated radiometric age (Rb-Sr and K-Ar) is 415 My. Palaeomagnetic north pole positions from the two complexes are 8°S 36° W ( A 95 = 5°) and 5° N 146° E ( A 95 = 23°) respectively. Complicated mineralogy and petrology reflect the hybrid character of the rocks. The magnetic minerals are correspondingly complex, but all are high temperature phases. Thermal and alternating field demagnetization, and variation of magnetic properties across a contact aureole, confirm the stability and primary origin of NRM in the complexes. Unbaked Dalradian rocks (12 cores) have no systematic NRM. Reconciliation of Siluro-Devonian data from Western Europe could involve persistent geomagnetic anomalies, large subsequent relative lateral movements between Britain and Norway, revision of geological or magnetic ages of various rocks studied palaeomagnetically, or either rapid shift or brief excursion of the ancient geomagnetic pole.